The Representation of Virtues and Vices of the Characters in Deadly 7 Inside Me (2021) - Fedrick Chandra; Theophilus Joko Riyanto (Institute of Research and Community Outreach - Petra Christian University, 2026)
This study explores how the virtues and vices of the main characters are represented in Deadly 7 Inside Me and why the main characters exercise them. This webtoon is interesting to analyze because of how it portrays the characters’ virtues and vices. Both Jonathan Haidt’s “Moral Foundation” theory and Carl Jung’s “Moral Dualism” theory are applied in the analysis. This study reveals that the main characters’ virtues and vices based on moral dualism, are aligned with the six moral foundations, which are Care/Harm, Loyalty/Betrayal, Fairness/Cheating, Authority/Subversion, Sanctity/Degradation, and Liberty/Oppression. This study also reveals that empathy, a sense of justice, lack of self-control, desire for dominance, and moral disobedience, trigger their virtues and vices. In conclusion, these findings show that people cannot be purely virtuous or vicious because they have virtues and vices within them.